A multiplex real-time PCR method for the quantitative determination of equine (horse) fractions in meat products. (April 2017) - Iwobi, A.; Sebah, D.; Spielmann, G.; Maggipinto, M.; Schrempp, M.; Kraemer, I.; Gerdes, L.; Busch, U.; Huber, I.
Abstract: The recent horse meat scandal that rocked Europe in early 2013 shows how important it is for the routine food control authorities to constantly evolve analytical tools for the accurate evaluation of meat products among others, to ensure that product declaration and actual composition correlate. While in most cases qualitative detection approaches suffice for product evaluation, in other cases a quantitative analysis is important to distinguish between inadvertent contamination and deliberate adulteration. In this work an optimized real-time qPCR-based approach is presented and compared with another real-time based method for the detection of equine sequences among others in meat products. The method is a multiplex system for the simultaneous quantification of horse, beef, pork and sheep fractions, and was validated for use in the routine analysis of meat products. We describe a modular multiplex approach, where a quadruplex system (without sheep) and a pentaplex assay (with an integrated sheep detection system) can be applied in meat detection and quantification strategies. The analysis is matrix independent and relies on concomitant quantification of the animal species present in the food sample against the backdrop of myostatin, a universal sequence present in most mammalian and poultry species. The limit of detection of the analytical method was 10 genome copy equivalents. For validation of the method, meat samples comprising differing meat compositions were analysed, and the assay performed well in terms of robustness and reproducibility. Highlights: A multiplex real-time qPCR system for quantitative assessment of meat is presented. Beef, pork, horse and sheep fractions quantified in relation to myostatin. Validation of the assay along recommended guidelines. Comparison with another real-time PCR method.